The village healer's book of cures - Roberts, Jennifer Sherman (Lake Union Publishing, 2023)
"Mary Fawcett refines the healing recipes she's inherited from generations of women before her--an uncanny and moral calling to empathize with the sick. When witchfinder Matthew Hopkins arrives in her small village, stoking the fires of hate, he sees not healing, but the devil at work. Mary's benevolent skills have now cast her and her young brother under suspicion of witchery. Soon, the husband of one of Mary's patients is found murdered, his body carved with strange symbols. For Hopkins, it's further evidence of dark arts. When the whispering village turns against her, Mary dares to trust a stranger: an enigmatic alchemist with a scarred body and soul, who knows the dead man's secrets. As Hopkin's fervor escalates, Mary must outsmart the devil himself to save her life and the lives of those she loves. Unfolding the true potential of her gifts could make Mary a more empowered adversary than a witchfinder ever feared." -page [4] of cover